Early Sports Specialization in Elite Wrestlers. (September 2019) - McDonald, Colin; Deitch, John; Bush, Chelsea
Background: Sports specialization is becoming an increasingly common training strategy in young athletes. Very little research currently exists examining the occurrence of serious injury (>3 months off sport or loss of season) in elite-level wrestlers who specialize early (before age 12 years). Hypothesis: Wrestlers who specialize early will sustain more serious injuries than wrestlers who specialize at age 12 years or older. Study Design: Descriptive epidemiological study. Methods: We sent an anonymous online survey to a total of 312 elite-level wrestlers (National Collegiate Athletic Association Division I athletes and World/Olympic team members) containing questions documenting age of specialization and number of serious injuries sustained. The number of serious injuries both before and after starting college were compared between wrestlers specializing at <12 years old and ≥12 years old using an independent-samples t test. Respondents' opinions on the necessity of early specialization and their primary source of encouragement to specialize were also reported. Results: A total of 143 wrestlers completed the survey, for a total response rate of 46%. Thirty-six (25%) wrestlers specialized at <12 years old. The early specialization group sustained significantly more serious injuries than the late specialization group (1.14 vs 0.60; P = 0.035). Sixty-two (43%) believed early specialization was necessary to achieve elite-level status. The decision to specialize was encouraged primarily by the athlete (78/143; 55%), parents (37/143; 26%), and coaches (22/143; 15%). Conclusion: Elite wrestlers who specialize prior to age 12 years sustain a greater number of serious injuries before starting college than those who specialize at or after the age of 12 years. Clinical Relevance: Athletes, coaches, and parents should consider the risk of injury before adopting a wrestling-specialized training strategy at a young age.